1986
DOI: 10.2105/ajph.76.4.407
|View full text |Cite
|
Sign up to set email alerts
|

The role of poultry and meats in the etiology of Campylobacter jejuni/coli enteritis.

Abstract: Consumption of chicken and cornish game hen were both associated with more than a doubling of the risk of CJC enteritis: for chicken (relative risk = 2.4, 95% CI = 1.6-3.6), and for game hen, (RR = 3.3, 95% CI = 1.1-9.8). The consumption of raw or rare chicken was even more strongly associated (RR = 7.6, 95% CI = 2.1-27.6). Strains of CJC bearing R factors for tetracycline were

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
115
0
2

Year Published

1992
1992
2010
2010

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 245 publications
(119 citation statements)
references
References 29 publications
2
115
0
2
Order By: Relevance
“…In contrast, the organism is a commensal of poultry, from which it enters the human food chain (Harris et al, 1986;Stern et al, 1988;Shane, 1992). In order to reduce the prevalence of C. jejuni in chickens, and thus decrease the risk of human infection, a better understanding of the factors involved in avian colonization is needed.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the organism is a commensal of poultry, from which it enters the human food chain (Harris et al, 1986;Stern et al, 1988;Shane, 1992). In order to reduce the prevalence of C. jejuni in chickens, and thus decrease the risk of human infection, a better understanding of the factors involved in avian colonization is needed.…”
Section: Introductionmentioning
confidence: 99%
“…Sporadic cases of campylobacteriosis are more common and are associated with the consumption of undercooked chicken. In the United States, case-control studies have attributed 48-70% of sporadic infections to the consumption of Campylobacter-contaminated chickens [11,15]. The percentage of Campylobactercontaminated chicken carcasses varies, often between 50 and 90%, depending on the time of year and the number of carcasses tested.…”
mentioning
confidence: 99%
“…It is this contamination of meat products that is believed to be the major source of campylobacteriosis in the human population (30). This belief is supported by case-control studies that have identified the consumption of untreated water, unpasteurized milk, and certain meats, often poultry, with the additional risk of campylobacteriosis (31)(32)(33)(34)(35).…”
Section: The Ecology Of Campylobacteriosismentioning
confidence: 96%